Influence of the form of axisymmetric load on the stress-strain state of an elastoplastic half-space - Ogar Peter; Gorokhov Denis; Mamaev Leonid; Kushnarev Vladislav (MATEC Web of Conferences, 2019)
The problems of elastic sinking of materials and elastic restoration of an imprint under loading of an elastic-plastic half-space with an axisymmetric load of the form,P(r)=P0(1-r2/a2)β where 0<β<0.5 are considered. Expressions are obtained that describing the stress-strain state of an elastoplastic half-space. The conditions of the onset of plastic deformation in the near-surface layer and on the half-space of surface are considered depending on the parameter β.